Application of three different sets of explicit criteria for assessing inappropriate prescribing in older patients: a nationwide prevalence study of ambulatory care visits in Taiwan. Issue 11 (6th November 2015) - Chang, Chirn-Bin; Yang, Shu-Yu; Lai, Hsiu-Yun; Wu, Ru-Shu; Liu, Hsing-Cheng; Hsu, Hsiu-Ying; Hwang, Shinn-Jang; Chan, Ding-Cheng
Abstract : Objective: To investigate the national prevalence of potentially inappropriate medications (PIMs) prescribed in ambulatory care clinics in Taiwan according to three different sets of regional criteria and the correlates of PIM use. Design: Cross-sectional study. Setting: This analysis included older patients who visited ambulatory care clinics in 2009 and represented half of the older population included on the Taiwanese National Health Insurance Research Database. Participants: We identified 1 164 701 subjects who visited ambulatory care clinics and were over 65 years old in 2009. Primary and secondary outcome measures: PIM prevalence according to the 2012 Beers criteria, the PIM-Taiwan criteria and the PRISCUS criteria was estimated separately, and characteristics of PIM users were explored. Multivariate logistic regression analysis was used to determine patient factors associated with the use of at least one PIM. Leading PIMs for each set of criteria were also listed. Results: The prevalence of having at least one PIM at the patient level was highest with the Beers criteria (86.2%), followed by the PIM-Taiwan criteria (73.3%) and the PRISCUS criteria (66.9%). Polypharmacy and younger age were associated with PIM use for all three sets of criteria. The leading PIMs detected by the PIM-Taiwan and PRISCUS criteria were all included in the 2012 Beers criteria. Non-COX-selective non-steroidal anti-inflammatory drugs in the Beers criteria and benzodiazepines in the PIM-Taiwan and PRISCUS criteria accounted for most leading PIMs. Conclusions: The prevalence of PIMs was high among older Taiwanese patients receiving ambulatory care visits. The prevalence of PIM and its associated factors varied according to three sets of criteria at the population level.